Testing Long-run Monetary Neutrality Proposition in ASEAN-5 Countries - Tang, Maggie May Jean. (Universiti Malaysia Sarawak (UNIMAS), 2012)
Long-run monetary neutrality hypothesis has been a debated issue in the field of monetary economics. Previously, most of the studies on long-run neutrality (LRN) proposition generally focused on simple sum monetary aggregate, the traditional monetary measurements. This study was carried out to test the neutrality proposition in the five ASEAN countries. A reduced form of neutrality test derived by Fisher and Seater (1993) was applied in this study. Two different types of monetary aggregates namely simple sum monetary aggregate and Divisia monetary aggregate were employed in this study in order to compare their relative performances as policy indicators. Empirical results revealed that LRN does not hold in ASEAN -5 countries except Thailand. Monetary aggregates seemed to have long-run effect on real output, thus central banks can use money supply as its alternative policy tools to stimulate the ....economic growth in their countries. Like the simple sum counterpart, Divisia monetary aggregates were found to be able to influence real output in the analyzed countries.